Future Rainfall Projections in Vietnam based on a CMIP6 Dynamical Downscaling Experiment - Duc Thanh, Ngo; Long, Trinh Tuan (VNU Journal of Science: Earth and Environmental Sciences; Vol 39 No 4DO - 10.25073/2588-1094/vnuees.4933, 2023)
This study presents, for the first time, the dynamical downscaled results at 25 km resolution for Vietnam from a global climate model participating in the Coupled Model Intercomparison Project Phase 6. The regional climate model (RegCM) version 4.7 was used with initial and boundary conditions from the global model CNRM-CM6-1 (referred to as CNRM) under the two Shared Socioeconomic Pathways (SSPs) 2-4.5 and 5-8.5. Simulated rainfall from RegCM and CNRM for the baseline period 1995–2014 is compared with the observation-based Vietnam Gridded Precipitation Dataset. The results indicate that downscaling is particularly effective in complex terrain areas, notably in the Central region during the winter monsoon season. However, in an overall assessment, the downscaled RegCM rainfall has not demonstrated added value compared to the CNRM results, whether in terms of annual variation, rainfall amounts, or spatial distribution. Future projection results until the end of the 21 st century show an increase in average rainfall, rainfall intensity, and annual maximum daily rainfall in Vietnam under both SSP2-4.5 and SSP5-8.5 scenarios. The increase is projected to reach approximately 25% in the Northern coastal area in the RegCM experiment under SSP5-8.5. The increase in rainfall intensity is pronounced across most of Vietnam, particularly under SSP5-8.5. Regarding projected maximum daily rainfall, there are discrepancies between the regional climate model and the global model. While CNRM exhibits unclear trends in many areas, RegCM indicates an overall increase in maximum daily rainfall across most of Vietnam under both SSPs scenarios.